Calcium phosphate /poly (ethylene glycol) bone cement: cell culture performance - Hablee, Sufiamie; Samsudin, Nurhusna; Sopyan, Lis; Mel, Maizirwan; Mohd. Salleh, Hamzah; Rahman, Md. Mujibur; Ahmad Raus, Raha (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Calcium phosphate cement (CPC) for injectable bone cement application has been developed in this study. The CPC was produced using a novel wet chemical precipitation method derived hydroxyapatite (HA) powder. The calcium and phosphorus precursors used to synthesize HA powder were calcium hydroxide, Ca(OH)2 , and di-ammonium hydrogen phosphate, (NH4 )2HPO4 . The HA powder was mixed with distilled water at certain powder-to-liquid (P/L) ratios. In this study, the P/L ratios were varied at 1.3 and 1.7. PEG was added into CPC with the P/L ratio of 1.3, and it was adjusted at 1 and 5 wt%. The results of this study revealed that higher P/L ratio contributed to the decreased in porosity of CPC. Meanwhile, the addition of PEG increased the porosity of CPC. This is significant for cells adhesion and proliferation, such that cell proliferate faster and better adhesion with the incorporation of PEG into CPC. The cell culture on CPC has proven that the fabricated CPC shows no toxic reaction and cells grow well.